2012
DOI: 10.1682/jrrd.2011.10.0207
|View full text |Cite
|
Sign up to set email alerts
|

Case report of modified Box and Blocks test with motion capture to measure prosthetic function

Abstract: Abstract-This case study report demonstrates the use of motion analysis with a modification of the Box and Blocks test. The goal was to quantify observed improvements in compensatory movements and simultaneous control in a subject using different prostheses before and after targeted muscle reinnervation (TMR) surgery. This is a single case study with data collection using a body-powered prosthesis pre-TMR surgery and 6 mo postfitting with a TMR myoelectric prosthesis. The Box and Blocks test was modified for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 23 publications
2
56
0
2
Order By: Relevance
“…In contrast, ACMC assesses how the prosthesis is normally used to assist the sound hand to perform bimanual activities. It has been reported that prosthesis users prefer to be assessed in their usual way of using the prosthesis [47], and consistent results are observed if they are allowed to perform the activities in their usual way [43]. Both assessment procedures are useful for different purposes, and it is important for clinicians to be aware of the different assessment procedures before they evaluate their clients.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, ACMC assesses how the prosthesis is normally used to assist the sound hand to perform bimanual activities. It has been reported that prosthesis users prefer to be assessed in their usual way of using the prosthesis [47], and consistent results are observed if they are allowed to perform the activities in their usual way [43]. Both assessment procedures are useful for different purposes, and it is important for clinicians to be aware of the different assessment procedures before they evaluate their clients.…”
Section: Discussionmentioning
confidence: 94%
“…Ten studies of varying quality and design (Table 4) suggest that, depending on functional needs, control scheme familiarity, and user preference, either BP with a conventional hook or MYO prostheses are advantageous compared with each other or other alternatives [9][10]17,21,24,29,[38][39][43][44]. The range of study designs supporting this statement includes expert opinion, observational, and experimental designs.…”
Section: Body-powered Upper-limb Prosthesesmentioning
confidence: 99%
“…For this reason, we previously used a modified version of the Box and Blocks (BB) test with motion capture to examine upper-limb prosthetic function and myoelectric control after targeted muscle reinnervation surgery [7]. We chose the BB test because it is a widely used, well-validated timed performance measure of upper-limb function [8] that requires repetitive consistent execution, with good responsiveness to change in performance [9].…”
Section: Introductionmentioning
confidence: 99%